Legal status of Couriers of diplomatic bags : analytical study - Adnan Abdullah Rasheed (QALAAI ZANIST SCIENTIFIC JOURNAL, 2020)
The mutual interrelationships between the persons of international law are the most characteristic of contemporary international life. The function of practicing these relationships it is the responsibility of the competent instituations to manage them. These relations are means (instrument) of practicing diplomatic and consular affairs that bind international entities together. The presence of these instituations is necessary under the emergence of unexpected problems among international entities, to mitigate their effects. All these issues will be through missions are specially formed to achieve the objectives, and these missions consist of two elements: personal and material. The first element includes: the chief of mission, staff…etc. The second element includes: mission office, mission archive, means of diplomatic communication…etc. Diplomatic means of communication include: diplomatic bag, electronic media…etc. Therefore, the diplomatic bag has an important role in the diplomatic action. No less important than what we said, the issue of how to transfer the diplomatic bag between countries. International law regulated this issue by studying what is a diplomatic bag? Or what should it include? Also, its immunity. International law was also concerned with regulated diplomatic couriers, their types and their immunities.